The Role of the Interventional Radiologist in Bile Leak Diagnosis and Management - Zhu, Yuli; Hickey, Ryan (Seminars in Interventional Radiology, 2021)
Bile leaks are rare but potentially devastating iatrogenic or posttraumatic complications. This is being diagnosed more frequently since the advent of laparoscopic cholecystectomy and propensity toward nonsurgical management in select trauma patients. Timely recognition and accurate characterization of a bile leak is crucial for favorable patient outcomes and involves a multimodal imaging approach. Management is driven by the type and extent of the biliary injury and requires multidisciplinary cooperation between interventional radiologists, endoscopists, and hepatobiliary/transplant surgeons. Interventional radiologists have a vital role in both the diagnosis and management of bile leaks. Percutaneous interventional procedures aid in the characterization of a bile leak and in its initial management via drainage of fluid collections. Most bile leaks resolve with decompression of the biliary system which is routinely done via endoscopic retrograde cholangiopancreaticography. Some bile leaks can be definitively treated percutaneously while others necessitate surgical repair. The primary principle of percutaneous management is flow diversion away from the site of a leak with the placement of transhepatic biliary drainage catheters. While this can be accomplished with relative ease in some cases, others call for more advanced techniques. Bile duct embolization or sclerosis may also be required in cases where a leaking bile duct is isolated from the main biliary tree.
Keywords: bile leak; percutaneous transhepatic cholangiography; bile duct injury